Використання штучних нейронних мереж для розпізнавання тексту на графічних зображеннях - Бандровський, Генріх (Видавництво Львівської політехніки, 2017)
The problem of natural scene image recognition has recently received much attention especially concerning the usage of neural networks in the context of machine learning. In this paper contemporary approaches towards pattern recognition problem are studied. Of special concern are the disadvantages of these approaches. The usage of convolutional neural network is analyzed.
Keywords: наука про дані; машинне навчання; машинний зір; розпізнавання образів; штучні нейронні мережі; штучний інтелект